Inactivation of TRP53, PTEN, RB1, and/or CDH1 in the ovarian surface epithelium induces ovarian cancer transformation and metastasis. Issue 5 (13th January 2020) - Shi, Mingxin; Whorton, Allison E; Sekulovski, Nikola; Paquet, Marilène; MacLean, James A; Song, Yurong; Van Dyke, Terry; Hayashi, Kanako
Abstract: Ovarian cancer (OvCa) remains the most common cause of death from gynecological malignancies. Genetically engineered mouse models have been used to study initiation, origin, progression, and/or mechanisms of OvCa. Based on the clinical features of OvCa, we examined a quadruple combination of pathway perturbations including PTEN, TRP53, RB1, and/or CDH1. To characterize the cancer-promoting events in the ovarian surface epithelium (OSE), Amhr2 cre/+ mice were used to ablate floxed alleles of Pten, Trp53, and Cdh1, which were crossed with TgK19GT121 mice to inactivate RB1 in KRT19-expressing cells. Inactivation of PTEN, TRP53, and RB1 with or without CDH1 led to the development of type I low-grade OvCa with enlarged serous papillary carcinomas and some high-grade serous carcinomas (HGSCs) in older mice. Initiation of epithelial hyperplasia and micropapillary carcinoma started earlier at 1 month in the triple mutations of Trp53, Pten, and Rb1 mice as compared to 2 months in quadruple mutations of Trp53, Pten, Rb1, and Cdh1 mice, whereas both genotypes eventually developed enlarged proliferating tumors that invaded into the ovary at 3–4 months. Mice with triple and quadruple mutations developed HGSC and/or metastatic tumors, which disseminated into the peritoneal cavity at 4–6 months. In summary, inactivation of PTEN, TRP53, and RB1 initiates OvCa from the OSE. Additional ablation of CDH1 further increased persistence of tumor dissemination and ascites fluid accumulation enhancing peritoneal metastasis. Abstract : Inactivation of TRP53, PTEN, and RB1 initiates ovarian cancer from the ovarian surface epithelium. Additional ablation of CDH1 further increased persistence of tumor dissemination.